Depressive Symptoms, Social Support and Employment: A Longitudinal Examination of Alcohol Use in Women - Laura D. Robinson; Isabella Ingram; Tayla J. Degan (Advances in Public Health)
Discussion: These findings underscore the importance of peer influence, mental health and stress associated with managing multiple responsibilities as key factors to address in targeting high-risk drinking behaviors among women. There is a clear need for more opportunities for women to assess their relationships with alcohol and seek help in the process. Addressing this issue is paramount, especially considering its increasing prevalence.